On the problem of renewal of a Poisson field on a plane - Zolotaya, A. V.; Shevlyakov, A. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We perform the renewal of a Poisson field at a point on the basis of its values generated by a monotonically increasing curve. We obtain the best mean-square estimate and its error.